Use of instantaneous profile and statistical methods to determine permeability functions of unsaturated soils - Krisdani, Henry (2011)
This paper presents the determination of permeability functions by direct and indirect methods. The direct method used in this study was the instantaneous profile method, while the indirect method used was the statistical method. The instantaneous profile method was adopted to calculate permeability functions of residual soils used in laboratory slope models. Pore-water pressure measured using tensiometers along the slope models and independently measured soil-water characteristic curves (SWCCs) were used for the instantaneous profile calculation. To obtain a continuous permeability function, the instantaneous profile results were then fitted using the statistical method.